2022
DOI: 10.1213/ane.0000000000006020
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Practice Trends and Perceptions Toward Postoperative Delirium: A Mixed-Methods Analysis

Abstract: Medicine. Support for underlying electronic health record data collection was provided, in part, by Blue Cross Blue Shield of Michigan (BCBSM) and Blue Care Network as part of the BCBSM Value Partnerships program for contributing hospitals in the state of Michigan. Although BCBSM and the Multicenter Perioperative Outcomes Group work collaboratively, the opinions, beliefs, and viewpoints expressed by the authors do not necessarily reflect the opinions, beliefs, and viewpoints of BCBSM or any of its employees. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Focus groups were conducted -and coded -by study team physicians (one male, one female) with prior focus group experience (J.R. and P.E.V.) using previously described methods [20]. These physicians lead a clinical research program that aims to optimize neurocognitive health in hospital inpatient settings.…”
Section: Methodsmentioning
confidence: 99%
“…Focus groups were conducted -and coded -by study team physicians (one male, one female) with prior focus group experience (J.R. and P.E.V.) using previously described methods [20]. These physicians lead a clinical research program that aims to optimize neurocognitive health in hospital inpatient settings.…”
Section: Methodsmentioning
confidence: 99%
“…Process measurement and compliance is important to increase the quality of care and therefore value, as even when evidence-based best practices are identified they may not be implemented. For example, previous studies have shown that few institutions “always” follow the Brain Trauma Foundation guidelines8 when managing patients with traumatic brain injury, nearly half of anesthesiologists were unaware of delirium prevention guidelines,9 and higher compliance with Enhanced Recovery After Surgery (ERAS) protocols was associated with improved outcomes 10. Ultimately, QI needs to be linked to relevant outcomes and cost efficiency to effectively drive value 6…”
Section: Value-based Health Care and Qi: Concepts And Frameworkmentioning
confidence: 99%